2013
DOI: 10.11118/actaun201361040893
|View full text |Cite
|
Sign up to set email alerts
|

Are the tendencies of the race to the bottom real in the European Union?

Abstract: The increasing globalization and integration of markets are one of the causes of tax competition. Even though tax competition may be beneficial for some countries, on the other hand for others states it may mean an erosion of their public budgets. The Member States are therefore forced to compete for a capital by a reducing of the tax burden (especially a cutting of the corporate effective tax rates) to don’t lose their tax bases. At present time of the debt crisis, when most of the Member States look for a so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The author found that there is no race to the bottom in all EU states, while such trends were detected only in the EU-12 group of new member countries. Taking into account that there is a considerable statistical dependence between the revenue from corporate income tax and the economic cycle, she supposed that the theory of the race to the bottom could be in phase with other factors in economy, notably if the economic growth could be observed in some countries, then the reduction of tax rates to a certain minimum threshold will not have a negative impact on revenue from corporate income tax [16].…”
Section: Issn 2412-8872mentioning
confidence: 99%
“…The author found that there is no race to the bottom in all EU states, while such trends were detected only in the EU-12 group of new member countries. Taking into account that there is a considerable statistical dependence between the revenue from corporate income tax and the economic cycle, she supposed that the theory of the race to the bottom could be in phase with other factors in economy, notably if the economic growth could be observed in some countries, then the reduction of tax rates to a certain minimum threshold will not have a negative impact on revenue from corporate income tax [16].…”
Section: Issn 2412-8872mentioning
confidence: 99%